Halogen-free flame-retardant packing belt and preparation method thereof

By using halogen-free composite flame retardant, modified montmorillonite, modified nano zinc oxide and continuous CF/PEEK prepreg powder in PP packaging tape, the problem of lack of flame retardant and fire-retardant characteristics and poor mechanical properties of the packaging tape is solved, and efficient flame retardant and fire-retardant effects and mechanical properties are achieved.

CN119859347AActive Publication Date: 2025-04-22TAIZHOU WEIDE PACKAGING CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510093677.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing PP packaging belt lacks flame retardant and fire-resistant characteristics, has a high slope, poor mechanical effect, short service life, and is prone to static electricity.

Method used

Halogen-free composite flame retardant, modified montmorillonite, modified nano zinc oxide and continuous CF/PEEK prepreg powder are used to prepare halogen-free flame retardant packaging belts with flame retardant effects, high crystallinity, low slope and mechanical effects through specific formulations and preparation methods.

Benefits of technology

The flame retardant and fire-retardant effect of the packaging belt is significantly improved, the crystallinity is improved, the slope is reduced, the mechanical properties are significantly improved, the service life is extended, and the use of halogen is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859347A_ABST
    Figure CN119859347A_ABST
Patent Text Reader

Abstract

The invention discloses a halogen-free flame-retardant packing belt and a preparation method thereof. The preparation method of the halogen-free flame-retardant packing belt comprises the following steps: S1, mixing polypropylene, an additive, a halogen-free composite flame retardant, a functional agent and a reinforcing agent to obtain a mixture; s2, pouring the mixture into an inner cavity of a screw extruder through a stock bin, and heating to 180-220 DEG C; s3, the materials in the step S2 are taken out of the extrusion die head and enter water to be cooled, and the temperature of the cooling water is controlled to be 38-42 DEG C; s4, performing primary stretching on the material cooled in the step S3, performing water cooling shaping, performing secondary stretching, and performing water cooling shaping; and S5, after the packing belt shaped in the step S4 passes through two press rollers with patterns, the patterns are pressed on the packing belt, and then cooling shaping, rolling, detecting, packaging and warehousing are conducted. Compared with the prior art, the prepared packing belt has the advantages of being good in flame retardant effect, good in mechanical effect and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of strapping tape materials, and in particular to a halogen-free flame-retardant strapping tape and a preparation method thereof. Background Art

[0002] PP strapping tape, scientifically known as polypropylene strapping tape, has been widely used in various fields because of its good plasticity, strong breaking tensile strength, bending resistance, light specific gravity, and easy use.

[0003] However, ordinary PP strapping tape is easily oxidized, has no flame retardant and fireproof properties, has a high deflection rate and poor actual use effect, and is also prone to static electricity, poor anti-deformation performance, and short service life.

[0004] CN112143096A discloses a lightweight PP strapping tape and a molding method thereof, which improves the performance of the strapping tape by adding polypropylene, fillers, colorants, and anti-aging agents. However, the PP strapping tape prepared by this method does not have the characteristics of flame retardancy and fireproofing.

[0005] CN111138762A discloses a method for preparing PP strapping tape, which improves the fire retardant performance by adding polypropylene, polyethylene terephthalate, butylated hydroxytoluene, toughening agent and flame retardant. However, the mechanical effect of the PP strapping tape prepared by this method may be poor. Summary of the invention

[0006] In view of the above-mentioned defects of the prior art, the purpose of the present invention is to provide a halogen-free flame retardant strapping tape, which has the characteristics of good flame retardant and fireproof effect, high crystallinity, low deflection rate and good mechanical effect.

[0007] One of the purposes of the present invention is to provide a halogen-free flame-retardant strapping tape, comprising the following raw materials: by weight, 100-120 parts of polypropylene, 1-6 parts of additives, 200-250 parts of halogen-free composite flame retardant, 5-10 parts of functional agent, and 5-10 parts of reinforcing agent.

[0008] Preferably, the additive is selected from montmorillonite and modified montmorillonite.

[0009] Further preferably, the preparation method of the modified montmorillonite comprises the following steps, measured in parts by weight:

[0010] Weigh 10-20 parts of dodecyl dimethyl benzyl ammonium bromide and add it to 100-200 parts of water, stir at 800-1000 rpm, heat to 80-100° C., add 50-100 parts of montmorillonite, continue stirring for 2-4 hours; cool, then centrifuge at 2000-4000 rpm for 5-10 minutes, wash the precipitate with water 3-6 times, dry at 60-80° C. for 6-8 hours, and crush through a 100-200 mesh sieve to obtain modified montmorillonite.

[0011] As a further illustration of the present invention, dodecyl dimethyl benzyl ammonium bromide can be used as a modifier to enter the molecular interlayer structure of montmorillonite through intercalation to obtain modified montmorillonite. The packing tape prepared by compounding the modified montmorillonite with materials such as polypropylene can form a stress transfer network, which is beneficial to improving its impact resistance and tensile strength. At the same time, the layered structure of the modified montmorillonite can isolate the penetration of gas and water molecules, which can improve the thermal stability and barrier properties of the composite material.

[0012] Preferably, the preparation method of the halogen-free composite flame retardant comprises the following steps, measured in parts by weight:

[0013] (1) Add 10-20 parts of phytic acid to 100-200 parts of water, mix and stir at room temperature and 800-1000 rpm to obtain solution A; add 10-20 parts of 1-phenylpiperazine to 100-200 parts of water, mix and stir at room temperature and 800-1000 rpm to obtain solution B;

[0014] (2) Heat solution A to 80-100°C, stir at 800-1000 rpm for 10-20 min, add solution B to solution A in 2-4 portions, add completely within 20-30 min, and then react for 20-40 min; then filter, wash the filter cake with 50-70°C water 4-6 times, and dry at 70-90°C for 16-24 h to obtain solid C;

[0015] (3) Mix 5-15 parts of solid C with 5-10 parts of polyetheramine, 10-15 parts of dimethylthiotoluene diamine, and 10-15 parts of 4,4'-methylenebis[N-sec-butylaniline] at 30-50° C. and stir evenly; then add 20-30 parts of polypropylene glycol and 20-40 parts of isophorone diisocyanate, continue mixing and stirring, and obtain a halogen-free composite flame retardant.

[0016] As a further illustration of the present invention, the halogen-free composite flame retardant can absorb heat from the surface of the strapping tape substrate, and release non-combustible gases such as NH3 and H2O through pyrolysis, which can dilute the surrounding oxygen concentration and have a certain extinguishing effect on the flame; on the other hand, the non-combustible gas NH3 produced can consume active free radicals in the gas phase and inhibit the combustion process. When the temperature continues to rise, the halogen-free composite flame retardant can absorb heat to generate acidic substances such as phosphoric acid and polyphosphoric acid, which react with 1-phenylpiperazine to undergo an esterification reaction. The esterification process will generate non-combustible gases such as NH3 and H2O, which will cause the molten system to expand and foam. When the reaction is nearly complete, the system solidifies and finally forms a dense expanded carbon layer. The expanded carbon layer can effectively inhibit the transfer of matter and energy between the combustion layer and the strapping tape, and hinder the pyrolysis of the lower material.

[0017] Preferably, the functional agent is selected from nano zinc oxide and modified nano zinc oxide.

[0018] Further preferably, the preparation method of the modified nano zinc oxide comprises the following steps, measured by weight:

[0019] 5-10 parts of ethyl glycolate and 10-20 parts of a modifier are mixed evenly, and then 0.1-1 parts of dibutyltin dilaurate are added, and the temperature is raised to 30-50°C, and the mixture is stirred at 800-1000rpm for 3-5h to obtain a mixed solution D; 10-20 parts of the mixed solution D, 1-5 parts of nano zinc oxide, 80-100 parts of anhydrous ethanol, and 40-50 parts of water are mixed, and the mixture is ultrasonically dispersed at 40-60kHz for 0.5-1.5h, and a 20-40wt% NaOH aqueous solution is added to adjust the pH to 9-11 to obtain a mixed solution E; the mixed solution E is stirred at 50-70°C and 800-1000rpm for 10-14h, and the mixture is filtered, and the precipitate is washed with anhydrous ethanol for 4-6 times, washed with water for 4-6 times, and dried at 60-80°C for 6-8h to obtain modified nano zinc oxide.

[0020] Preferably, the modifier is selected from at least one of methacryloxypropyl tris(trimethylsiloxy)silane, isocyanatepropyl triethoxysilane and pentafluorophenyl triethoxysilane.

[0021] As a further illustration of the present invention, the aging process of PP strapping tape is mainly caused by the generation of active free radicals induced by the external environment. The free radicals continuously induce chain reactions in an oxygen environment, thereby breaking the polypropylene molecular chain and eventually causing degradation. The present invention introduces modified nano zinc oxide and polypropylene to prepare a halogen-free flame-retardant strapping tape. The modified nano zinc oxide has a high ultraviolet absorption rate and can protect against ultraviolet damage. At the same time, the modified nano zinc oxide can slow down the chain reaction by capturing free radicals, thereby reducing the aging rate of polypropylene. In addition, the modified nano zinc oxide can also be used as a nucleating agent to improve the crystallinity of the strapping tape and promote the tensile strength, dimensional stability and temperature resistance of the strapping tape.

[0022] Preferably, the reinforcing agent is continuous CF / PEEK prepreg powder; the preparation method of the continuous CF / PEEK prepreg powder comprises the following steps, measured in parts by weight: by weight, 10-20 parts of continuous CF / PEEK prepreg are crushed through a 100-200 mesh sieve to obtain continuous CF / PEEK prepreg powder.

[0023] As a further illustration of the present invention, continuous CF / PEEK prepreg powder has the advantages of light weight, high strength, corrosion resistance, anti-aging, high temperature resistance, etc. Adding continuous CF / PEEK prepreg powder can improve the mechanical properties and temperature resistance of the strapping tape, and can also induce crystallization, increase the crystallinity of the strapping tape, and improve the dimensional stability.

[0024] The second object of the present invention is to provide a method for preparing the above-mentioned halogen-free flame-retardant strapping tape, comprising the following steps:

[0025] S1. Mixing polypropylene, additives, halogen-free composite flame retardant, functional agent and reinforcing agent to obtain a mixture;

[0026] S2, pouring the mixed material into the inner cavity of the screw extruder through the silo, heating the temperature to 180-220°C to obtain the material;

[0027] S3, taking the material in step S2 out of the extrusion die head and cooling it in water, wherein the cooling water temperature is controlled at 38-42° C. to obtain a cooled material;

[0028] S4, stretching the material after cooling in step S3 once and then cooling it with water to shape it, and then stretching it twice and then cooling it with water to shape it, so as to obtain a shaped packing tape;

[0029] S5, passing the strapping tape formed in step S4 through two patterned pressing rollers, after the pattern is pressed, cooling and shaping, winding, testing, packaging, and storage, to obtain a halogen-free flame-retardant strapping tape.

[0030] The beneficial effects of the present invention are as follows:

[0031] 1. The packing tape prepared by the inventor using the formula materials and method provided by the present invention has high uniformity in thickness and width and low skewness.

[0032] 2. Compared with the prior art, the strapping tape prepared by adding modified montmorillonite, halogen-free composite flame retardant, modified nano zinc oxide and continuous CF / PEEK prepreg powder in the present invention has good flame retardant and fireproof effect, high crystallinity, low deflection rate and good mechanical effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Attached Figure 1 For product pictures. DETAILED DESCRIPTION

[0034] The parameters and sources of some raw materials in the embodiments of the present invention are as follows:

[0035] Polypropylene, grade: P740J, brand: Siam, Thailand;

[0036] Montmorillonite, surface area 240m 2 / g;

[0037] Nano zinc oxide, particle size: 50±10nm;

[0038] Polyetheramine, product number: P939193, MW ~ 2000, EO / PO ratio: 6 / 29, from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0039] 1-Phenylpiperazine, CAS No.: 92-54-6;

[0040] Polypropylene glycol, average molecular weight 4000;

[0041] Continuous CF / PEEK prepreg, material grade: LU-CF / PEEK, carbon fiber content, 66%, from Jiangsu Junhua Special Polymer Materials Co., Ltd. CF refers to carbon fiber, PEEK refers to polyetheretherketone.

[0042] Example 1

[0043] A method for preparing a halogen-free flame-retardant strapping tape comprises the following steps:

[0044] S1. Mix 110 g of polypropylene, 4 g of modified montmorillonite, 230 g of halogen-free composite flame retardant, 8 g of modified nano zinc oxide, and 8 g of continuous CF / PEEK prepreg powder to obtain a mixture;

[0045] S2, pour the mixed material into the inner cavity of the screw extruder through the silo, and heat the temperature to 200°C;

[0046] S3, taking the material in step S2 out of the extrusion die head and cooling it in water, and the cooling water temperature is controlled at 40°C;

[0047] S4, the material cooled in step S3 is first stretched once and then water-cooled to set the shape, and then stretched twice and then water-cooled to set the shape;

[0048] S5, passing the strapping tape formed in step S4 through two patterned pressing rollers, after the pattern is pressed, cooling and shaping, winding, testing, packaging and storage.

[0049] The modified montmorillonite is prepared by the following method:

[0050] Weigh 15g of dodecyldimethylbenzyl ammonium bromide and add it to 150g of water. After heating to 90°C at 900rpm, add 80g of montmorillonite and continue stirring and heating for 3h. After cooling, centrifuge at 3000rpm for 8min, wash the precipitate with water 5 times, dry at 70°C for 7h, and crush it through a 200-mesh sieve to obtain modified montmorillonite.

[0051] The halogen-free composite flame retardant is prepared by the following steps:

[0052] (1) Add 15 g of phytic acid to 150 g of water, and stir at room temperature at 900 rpm to obtain solution A; add 15 g of 1-phenylpiperazine to 150 g of water, and stir at room temperature at 900 rpm to obtain solution B;

[0053] (2) Solution A was heated to 90°C and stirred at 900 rpm for 10 min. Solution B was added to Solution A in three portions within 25 min, followed by reaction for 30 min. The filter cake was then washed with 60°C water for 5 times and dried at 80°C for 20 h to obtain solid C.

[0054] (3) Mix 10 g of solid C with 7 g of polyetheramine, 12 g of dimethylthiotoluene diamine, and 13 g of 4,4'-methylenebis[N-sec-butylaniline] at 40° C. Then add 25 g of polypropylene glycol and 25 g of isophorone diisocyanate, and continue mixing and stirring to obtain a halogen-free composite flame retardant.

[0055] The modified nano zinc oxide is prepared by the following method:

[0056] 7.5 g of ethyl glycolate and 15 g of pentafluorophenyltriethoxysilane were mixed evenly, and after adding 0.5 g of dibutyltin dilaurate, the temperature was raised to 40°C, and stirred at 900 rpm for 4 hours to obtain a mixed solution D; 15 g of the mixed solution D, 3 g of nano zinc oxide (particle size: 50±10 nm), 90 g of anhydrous ethanol, and 45 g of water were mixed, ultrasonically dispersed at 50 kHz for 1.0 hour, and a 30 wt% NaOH aqueous solution was added to adjust the pH to 10 to obtain a mixed solution E; the mixed solution E was stirred at 60°C and 900 rpm for 12 hours, filtered, and the precipitate was washed 5 times with anhydrous ethanol, washed 5 times with water, and dried at 70°C for 7 hours to obtain modified nano zinc oxide.

[0057] The continuous CF / PEEK prepreg powder is prepared by the following method:

[0058] 15 g of continuous CF / PEEK prepreg was crushed and passed through a 200-mesh sieve to obtain continuous CF / PEEK prepreg powder.

[0059] Example 2

[0060] A method for preparing a halogen-free flame-retardant strapping tape, which differs from Example 1 in that 4 g of modified montmorillonite in step S1 is replaced by 4 g of montmorillonite.

[0061] Example 3

[0062] A method for preparing a halogen-free flame-retardant strapping tape, which differs from Example 1 in that 230 g of the halogen-free composite flame retardant in step S1 is replaced with 230 g of a halogen-free composite flame retardant prepared by the following method.

[0063] The halogen-free composite flame retardant is prepared by the following steps:

[0064] 10g of triphenyl phosphate was mixed evenly with 7g of polyetheramine, 12g of dimethylthiotoluenediamine and 13g of 4,4'-methylenebis[N-sec-butylaniline] at 40°C; 25g of polypropylene glycol and 25g of isophorone diisocyanate were added and mixed to obtain a halogen-free composite flame retardant.

[0065] Example 4

[0066] A method for preparing a halogen-free flame-retardant strapping tape, which differs from Example 1 in that the modified nano zinc oxide in step S1 is prepared by the following method:

[0067] 7.5 g of ethyl glycolate and 15 g of isocyanatepropyltriethoxysilane were mixed evenly, and after adding 0.5 g of dibutyltin dilaurate, the temperature was raised to 40°C, and stirred at 900 rpm for 4 hours to obtain a mixed solution D; 15 g of mixed solution D, 3 g of nano zinc oxide (particle size: 50±10 nm), 90 g of anhydrous ethanol, and 45 g of water were mixed, ultrasonically dispersed at 50 kHz for 1.0 hour, and a 30 wt% NaOH aqueous solution was added to adjust the pH to 10 to obtain a mixed solution E; the mixed solution E was stirred at 60°C and 900 rpm for 12 hours, filtered, and the precipitate was washed 5 times with anhydrous ethanol, washed 5 times with water, and dried at 70°C for 7 hours to obtain modified nano zinc oxide.

[0068] Example 5

[0069] A method for preparing a halogen-free flame-retardant strapping tape, which differs from Example 1 in that the modified nano zinc oxide in step S1 is prepared by the following method:

[0070] 7.5 g of ethyl glycolate and 15 g of methacryloyloxypropyl tri(trimethylsiloxy)silane were mixed evenly, and after 0.5 g of dibutyltin dilaurate was added, the temperature was raised to 40°C, and stirred at 900 rpm for 4 hours to obtain a mixed solution D; 15 g of the mixed solution D, 3 g of nano zinc oxide (particle size: 50±10 nm), 90 g of anhydrous ethanol, and 45 g of water were mixed, ultrasonically dispersed at 50 kHz for 1.0 hour, and a 30 wt% NaOH aqueous solution was added to adjust the pH to 10 to obtain a mixed solution E; the mixed solution E was stirred at 60°C and 900 rpm for 12 hours, filtered, and the precipitate was washed 5 times with anhydrous ethanol, washed 5 times with water, and dried at 70°C for 7 hours to obtain modified nano zinc oxide.

[0071] Comparative Example 1

[0072] A method for preparing a halogen-free flame-retardant strapping tape, which differs from Example 1 in that 230 g of the halogen-free composite flame retardant in step S1 is replaced by a mixture of 230 g of the halogen-free composite flame retardant consisting of 10 g of triphenyl phosphate and 220 g of polypropylene.

[0073] Test Example 1

[0074] Performance Testing

[0075] The strapping tapes of Examples 1-5 and Comparative Example 1 have a specification of 12 mm in width and 0.6 mm in thickness, and performance tests were performed on each of the Examples and Comparative Example.

[0076] Test method:

[0077] 1. Measure the skewness according to the method of "QB / T3811-1999 Plastic Strapping Tape".

[0078] 2. According to the method of GB / T32340-2015 Polyester Strapping for Cotton Packaging, test the longitudinal cracking, the number of cracking points is n / 10, the smaller the n value, the better the performance of the strapping tape.

[0079] 3. According to GB / T2408-2021 Horizontal and Vertical Methods for Determination of Combustion Performance of Plastics, a vertical combustion experiment is carried out to determine the flame retardant grade; the xenon lamp aging method is: after a 1200h xenon lamp aging test at a wavelength of 420nm in accordance with GB / T16422.2-2022 Plastic Laboratory Light Source Exposure Test Method, a vertical combustion experiment is carried out again in accordance with GB / T2408-2008 Horizontal and Vertical Methods for Determination of Combustion Performance of Plastics.

[0080] The test results are shown in Table 1 below.

[0081] Table 1

[0082]

[0083]

[0084] By comparing Examples 1-5 with Comparative Example 1, it can be found that Example 1 has the lowest width deviation, thickness deviation and skewness. The possible reason is that the material quality used in Example 1 is stable and the slurry obtained is uniform. The combination of materials used and the preparation process provide a more stable size of the strapping tape, so the skewness is lower.

[0085] By comparing Examples 1-5 with Comparative Example 1, it can be found that the longitudinal cracking of Example 1 is low. The possible reason is that the strapping tape prepared by compounding modified montmorillonite with polypropylene and other materials added in Example 1 can form a stress transfer network to improve its impact resistance and tensile strength, thereby improving the mechanical effect; the added halogen-free composite flame retardant not only has a flame retardant effect, but also has a polyurea structure with high tensile strength and tear strength, thereby improving the mechanical effect of the strapping tape; modified nano zinc oxide and continuous CF / PEEK prepreg powder can act as heterogeneous nucleating agents to induce crystallization, and the crystalline region acts as a physical cross-linking point to enhance the interaction between molecules, enhance the tensile strength, and improve the mechanical effect.

[0086] By comparing Examples 1-5, it can be found that the flame retardant grade of Example 1 is higher after light aging. The possible reason is that the modified montmorillonite added in Example 1 can isolate the penetration of gas and water molecules and improve the thermal stability and barrier properties of the composite material; the halogen-free composite flame retardant releases non-flammable gases such as NH3 and H2O during pyrolysis, which can dilute the surrounding oxygen concentration. After pyrolysis, the system solidifies to form a dense expanded carbon layer, which can effectively inhibit the transfer of matter and energy between the combustion layer and the strapping tape and hinder the pyrolysis of the material; pentafluorophenyl triethoxysilane-modified nano zinc oxide has a better effect on absorbing ultraviolet light, capturing free radicals, and slowing down chain reactions, thereby reducing the aging rate of the strapping tape.

[0087] Test Example 2

[0088] Crystallinity test

[0089] DSC tests were performed on the strapping tape samples prepared in Examples 1-5 of the present invention and Comparative Example 1, respectively. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg. The heating and cooling rates were both 10 K / min. The crystallinity of the samples was tested. The test results are shown in Table 2.

[0090] Table 2

[0091]

[0092] By comparing Examples 1-5 with Comparative Example 1, it can be found that Example 1 has the highest crystallinity. The possible reason is that the modified montmorillonite added in Example 1 can form a confined space, reduce the nucleation activation energy and improve the crystallinity; it may be that the surface activity of pentafluorophenyl triethoxysilane-modified nano zinc oxide is higher, and the binding effect with the polypropylene molecular chain is better. As a nucleating agent, it provides crystal nuclei for the crystallization of the polypropylene molecular chain, and the effect of promoting crystallization is better; the continuous CF / PEEK prepreg powder has a regular fiber structure, which can be used as a physical cross-linking point to enhance the interaction between molecules and promote the crystallization of polypropylene.

Claims

1. A halogen-free flame-retardant strapping tape, characterized in that: The raw material components include 100-120 parts of polypropylene, 1-6 parts of additives, 200-250 parts of halogen-free composite flame retardant, 5-10 parts of functional agent and 5-10 parts of reinforcing agent by weight.

2. The halogen-free flame-retardant strapping tape according to claim 1, characterized in that: The additive is selected from montmorillonite and modified montmorillonite.

3. The halogen-free flame-retardant strapping tape according to claim 2, characterized in that: The preparation method of the modified montmorillonite comprises the following steps, calculated by weight: Weigh 10-20 parts of dodecyldimethylbenzyl ammonium bromide and add it to 100-200 parts of water, stir at 800-1000rpm, heat to 80-100℃, add 50-100 parts of montmorillonite, continue stirring for 2-4h; cool, then centrifuge at 2000-4000rpm for 5-10min, wash the precipitate with water 3-6 times, dry at 60-80℃ for 6-8h, and crush through a 100-200 mesh sieve to obtain modified montmorillonite.

4. The halogen-free flame-retardant strapping tape according to claim 1, characterized in that: The preparation method of the halogen-free composite flame retardant comprises the following steps, calculated by weight: (1) Add 10-20 parts of phytic acid to 100-200 parts of water, mix and stir at room temperature and 800-1000 rpm to obtain solution A; add 10-20 parts of 1-phenylpiperazine to 100-200 parts of water, mix and stir at room temperature and 800-1000 rpm to obtain solution B; (2) Heat solution A to 80-100°C, stir at 800-1000 rpm for 10-20 min, add solution B to solution A in 2-4 portions, add completely within 20-30 min, and then react for 20-40 min; then filter, wash the filter cake with 50-70°C water 4-6 times, and dry at 70-90°C for 16-24 h to obtain solid C; (3) Mix 5-15 parts of solid C with 5-10 parts of polyetheramine, 10-15 parts of dimethylthiotoluene diamine, and 10-15 parts of 4,4'-methylenebis[N-sec-butylaniline] at 30-50° C. and stir evenly; then add 20-30 parts of polypropylene glycol and 20-40 parts of isophorone diisocyanate, continue mixing and stirring, and obtain a halogen-free composite flame retardant.

5. The halogen-free flame-retardant strapping tape according to claim 1, characterized in that: The functional agent is selected from one of nano zinc oxide and modified nano zinc oxide.

6. The halogen-free flame-retardant strapping tape according to claim 5, characterized in that: The preparation method of the modified nano zinc oxide comprises the following steps, calculated by weight: 5-10 parts of ethyl glycolate and 10-20 parts of a modifier are mixed evenly, and then 0.1-1 parts of dibutyltin dilaurate are added, and the temperature is raised to 30-50°C, and the mixture is stirred at 800-1000rpm for 3-5h to obtain a mixed solution D; 10-20 parts of the mixed solution D, 1-5 parts of nano zinc oxide, 80-100 parts of anhydrous ethanol, and 40-50 parts of water are mixed, and the mixture is ultrasonically dispersed at 40-60kHz for 0.5-1.5h, and a 20-40wt% NaOH aqueous solution is added to adjust the pH to 9-11 to obtain a mixed solution E; the mixed solution E is stirred at 50-70°C and 800-1000rpm for 10-14h, and the mixture is filtered, and the precipitate is washed with anhydrous ethanol for 4-6 times, then washed with water for 4-6 times, and then dried at 60-80°C for 6-8h to obtain modified nano zinc oxide.

7. A halogen-free flame-retardant strapping tape as claimed in claim 6, characterized in that: The modifier is selected from at least one of methacryloxypropyl tris(trimethylsiloxy)silane, isocyanatepropyl triethoxysilane and pentafluorophenyl triethoxysilane.

8. The halogen-free flame-retardant strapping tape according to claim 1, characterized in that: The reinforcing agent is continuous CF / PEEK prepreg powder; the preparation method of the continuous CF / PEEK prepreg powder comprises the following steps, calculated by weight: 10-20 portions of continuous CF / PEEK prepreg are crushed and passed through a 100-200 mesh sieve to obtain continuous CF / PEEK prepreg powder.

9. A method for preparing a halogen-free flame-retardant strapping tape according to any one of claims 1 to 8, characterized in that: The steps include: S1. Mixing polypropylene, additives, halogen-free composite flame retardant, functional agent and reinforcing agent to obtain a mixture; S2, pouring the mixed material into the inner cavity of the screw extruder through the silo, heating the temperature to 180-220°C to obtain the material; S3, taking the material in step S2 out of the extrusion die head and cooling it in water, wherein the cooling water temperature is controlled at 38-42° C. to obtain a cooled material; S4, stretching the material after cooling in step S3 once and then cooling it with water to shape it, and then stretching it twice and then cooling it with water to shape it, so as to obtain a shaped packing tape; S5, passing the strapping tape formed in step S4 through two patterned pressing rollers, after the pattern is pressed, cooling and shaping, winding, testing, packaging, and storage, to obtain a halogen-free flame-retardant strapping tape.

Citation Information

Patent Citations

  • Light PP packing belt and forming processing method thereof

    CN112143096A

  • Flame retardant material and preparation method thereof and automobile engine trim cover

    CN102993564A

  • Halogen-free flame-retardant antibacterial anti-aging polypropylene composite material and preparation method thereof

    CN103992562A

  • Ammonium phytate flame retardant, preparation method thereof and flame retardant and toughened polylactic acid material

    CN108047494A

  • Preparation method of PP packing belt

    CN111138762A